Melodies of empowerment: Unearthing ideological themes in Maguindanaon’s protest songs through stylistic analysis - Maulana, Saima S.; Parcon, Marissa N.; Untong, Leonel P.; Parcon, Baisoraya S.; Mamidted, Asgar D.; Bawa, Lydia S. (Edelweiss Applied Science and Technology, 2024)
This qualitative study employing stylistic analysis probed the stylistic architecture of Bangsamoro protest songs concerning semantics levels of language and investigated how this stylistic architecture foregrounds the embedded ideologies of protest songs. Fifty-one protest songs written in the Maguindanaon language served as the research material. The findings of the study showed that semantics devices such as allegory, apostrophe, climax, euphemism, hyperbole, visual imagery, irony, metaphor, personification, satire, simile, symbol, proverb, and idiom were manifested. Additionally, the civil rights movement, peace movement, anti-war movement, and anti-authoritarian movement ideologies were identified as the embedded ideologies foregrounded by the stylistic architectures found in the Bangsamoro protest songs. Therefore, analyzing and reflecting on the message of protest songs helps listeners understand social and political issues.